Rare Presentation of Hypoparathyroidism with Feautures of Parkinsonism: A Case Report - Kharel, S; Shrestha, S; Pokharel, A (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
This case report presents a 54-year-old female diagnosed with Hypoparathyroidism, manifesting with symptoms of Parkinsonism. The report details the patient’s clinical presentation, diagnostic journey, and management strategies. Recognizing the diverse presentations and implementing appropriate management protocols are essential for achieving timely diagnosis and effective treatment in Hypoparathyroidism cases.